Editorial, Volume 11 Issue 1 - Kristy L Archuleta (Journal of Financial Therapy, 2020)
Of any field, financial therapy is uniquely positioned to help people, whether individuals, couples, or families, strengthen, adapt, and improve their wellness during this time. Financial therapists are sensitive to cultural aspects of how money impacts clients’ everyday lives. Through our unique understanding and knowledge of the intersection of money, relationships, emotions, and ways of thinking and being, we can facilitate change and offer new perspectives of hope, connection, and personal growth. While none of the articles in this issue of the journal directly address the global pandemic, the research presented and profiles highlighted do offer new insights on topics that can help professionals improve overall and financial well-being.
Keywords: financial therapy